THE STRATEGY OF MIND MAPPING IN TEACHING DESCRIPTIVE WRITING THROUGH THE FOURTH SEMESTER STUDENTS AT STIKOM TUNAS BANGSA IN PEMATANGSIANTAR - Sormin, Rizky Khairunnisa; Purnama, Ika; Purba, Anita (Politeknik Negeri Jakarta, 2024)
Writing is one of the four aspects of language skills that a person must possess. Using writing, someone can generate interesting ideas and pour them into writing. Writing descriptive paragraphs is also one of the lessons that the school student finds difficult to understand; the mind mapping method is applied to see how the technique influences writing students, especially in the description text. This study aims to examine the import of image media-based mind mapping on the fourth-semester students' skills in writing descriptive text paragraphs. The subjects are fourth-grade students at STIKOM Tunas Bangsa. The research adopts a mixed-methods framework, merging qualitative and quantitative approaches to examine the intervention’s outcomes comprehensively. The quantitative component includes pre-tests and post-tests to assess improvements in students' descriptive writing skills before and after the intervention of image media-based mind-mapping. The qualitative component consists of classroom observations, student feedback, and analysis of written assignments to capture students' experiences and perceptions of the technique. Results indicate that the image media-based mind mapping technique significantly enhances students' ability to generate ideas, organize their writing, and incorporate detailed descriptions. The study highlights the effectiveness of combining visual media with mind mapping to improve descriptive writing, suggesting that this approach offers a valuable tool for educators aiming to enhance student's writing proficiency where students view mind mapping positively, nothing its effectiveness in highlighting critical information from the textbook and simplifying the process of understanding details.